Childhood Physical and Sexual Violences as Potential Factors of Post Traumatic Stress Disorder: A Meta-Analysis - Fadila Alfiasari; Didik Tamtomo; Hanung Prasetya (Journal of Epidemiology and Public Health, 2023)
Background: WHO states that as many as 300 million children have experienced physical punishment or psychological violence. These traumatic events can cause Post Traumatic Stress Disorder (PTSD) which has an impact on the lives of victims of physical and sexual violence. The purpose of this study was to analyze and estimate the average influence of physical and sexual violence in childhood on the incidence of Post Traumatic Stress Disorder (PTSD) using a meta-analysis study.Subjects and Method: This research is a systematic review and meta-analysis with the selection of PRISMA flow diagrams. Population= adults aged >18 years. Intervention= experience of physical and sexual violence as children. Comparison= no experience of physical and sexual violence as children. Outcome= PTSD. Article searches through journal databases include: Pubmed, Google Schoolar, Science Direct, Researchgate and Springerlink. The articles used in this study are articles that have been published from 2000-2022. The keywords used in the database are “Child Physical Abuse”[tw] OR “Childhood Physical Abuse”[tw] OR “Child Maltreatment”[tw] OR “Physical Violence”[tw] OR "Physical Abuse"[Mesh] OR " Child Abuse"[Mesh] AND “Sexual Abuse”[tw] OR “Child Sexual Molestation”[tw] OR "Child Abuse, Sexual"[Mesh] OR "Sexual Trauma"[Mesh] AND “Post-Traumatic Stress Disorder*” [tw] OR “Posttraumatic Stress Disorder*” OR “Post-Traumatic Neuroses”[tw] OR “Post-traumatic Neuroses”[tw] OR “PTSD”[tw] OR "Stress Disorders, Post-Traumatic"[Mesh]. Inclusion criteria included full-text articles with a cross-sectional study design. The analysis used multivariate logistic regression with adjusted Odds Ratio and published in English. Articles that met the requirements were analyzed using the Revman 5.4 application.Results: Meta-analysis of 10 articles showing for childhood physical abuse (aOR=1.87; 95% CI=1.47 to 2.37; p<0.001) and childhood sexual violence (aOR=2.67; 95% CI=2.02 up to 3.52; p<0.001).Conclusion: Experience of physical and sexual violence in childhood increases the risk of developing Post Traumatic Stress Disorder as an adult. Keywords: Post Traumatic Stress Disorder, physical violence, sexual violence, meta-analysis Correspondence: Fadila Alfiasari. Masters Program in Public Health, Universitas Sebelas maret. Jl. Ir. Sutami 36A, Surakarta 57126, Jawa Tengah, Indonesia. Email: alfiasari3108@gmil.com. Mobile: +6285235358882.